Implementasi Pembelajaran Model Project Based Learning Pendekatan STEAM Untuk Melatihkan Keterampilan Berpikir Kritis Peserta Didik - Rachmawati, Tsaniyah Nabilah; Andy, Agus; Zainuddin, Abu; Munasir, Munasir (Universitas Negeri Surabaya, 2023)
This study aims to train critical thinking skills and improve students' critical thinking skills, by conducting project-based learning with a science, technology, engineering, arts, and mathematic (STEAM) approach. This research is applied to x-grade students and carried out at SMA Negeri 1 Wonoayu Sidoarjo. This study use a classroom action research design conducted over two cycles. Each cycle uses the pre-experimental design method of one group pretest-posttest. Data collection techniques use observation, and tests, which are then analyzed using non-parametric tests. The results of this study show that students' critical thinking skills increased after learning PJBL STEAM for two cycles. The project is carried out related to alternative energy content with the manufacture of solar automatic garden lights. The first cycle pretest-posttest increases from the low category to the sufficient category, and the second cycle seen an average increase between the pretest and posttest of 12.08%. Critical thinking skills must continue to be consistently trained in order to get maximum results, critical thinking can be trained with the right methods and innovations. Keywrods : Critical Thinking, Project Based Learning, STEAM.